2017
DOI: 10.1103/physreva.96.042705
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Feshbach resonances in ultracold scattering calculations

Abstract: Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncommercial personal purposes. Except as provided by law, this material may not be further reproduced, distributed, transmitted, modi ed, adapted, performed, displayed, published, or sold in whole or part, without prior written permission from the American Physical Society.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…molscat can converge on and characterise the zero-energy Feshbach resonances that appear in the scattering length as a function of external fields [10]. It can do this for resonances both in elastic scattering, where the scattering length has a simple pole characterised by its position and width and the background scattering length, and in inelastic scattering, where the resonant behaviour is more complex and requires additional parameters [9].…”
Section: Characterisation Of Zero-energy Feshbach Resonancesmentioning
confidence: 99%
“…molscat can converge on and characterise the zero-energy Feshbach resonances that appear in the scattering length as a function of external fields [10]. It can do this for resonances both in elastic scattering, where the scattering length has a simple pole characterised by its position and width and the background scattering length, and in inelastic scattering, where the resonant behaviour is more complex and requires additional parameters [9].…”
Section: Characterisation Of Zero-energy Feshbach Resonancesmentioning
confidence: 99%
“…This is analogous to the "fully complex" procedure of Ref. [9] and allows convergence on E res and Γ as well as S bg,ii and D ii . In multichannel scattering, we have sometimes found that this procedure converges successfully, even for resonances where uncorrected energy dependence in the background prevents convergence based on the eigenphase sum.…”
Section: Partial Widthsmentioning
confidence: 94%
“…One of the outer points is placed about Γt lo from E res (with tolerance ±ξΓt lo ), and the other is about Γt hi from it (with tolerance ±ξΓt hi ). This strategy is similar to that in our procedures for converging on a zero-energy Feshbach resonance as a function of external field [9]. The three points can be regarded as allowing characterization of E res , Γ, and δ bg , respectively.…”
Section: Theorymentioning
confidence: 99%
“…Recently, Fryeet al [72] published a procedure for extracting parameters, namely the positions B res , widths ΔB, and background scattering lengths a bg , of Feshbach resonances that conform to the Breit-Wigner profile,…”
Section: Zero-field Scattering Lengths and Feshbach Spectramentioning
confidence: 99%